ANTECEDENTS OF ONLINE EXPERIENCE ON E-COMMERCE PLATFORM IN INDONESIA - Edwin Kangagung; Nony Kezia Marchyta (Institute of Research and Community Outreach - Petra Christian University, 2022)
The developments of online technology in Indonesia had transformed how businesses approach Indonesian customers, leading to the rise of e-commerce. This research was conducted by distributing questionnaires to 196 respondents who are a leading e-commerce platform in Indonesia. Multiple regression analysis had been used to test the hypotheses. The study found that perceived usability, perceived enjoyment, and online social interaction had a significant positive effect on the online experience. This study helps online shopping platforms to understand the opportunity to enhance the online experience of their customers. Abstrak: Perkembangan teknologi online di Indonesia telah mengubah cara bisnis dalam memikat pelanggan, yang mengarah pada lahirnya e-commerce. Penelitian ini dilakukan dengan mendistribusikan angket penelitian kepada 196 responden dari salah satu platform e-commerce terkemuka di Indonesia. Analisis regresi berganda digunakan untuk menguji hipotesis penelitian. Hasil penelitian ini menunjukkan bahwa perceived usability, perceived enjoyment, dan online social interaction memiliki pengaruh positif terhadap online experience. Hasil penelitian ini membantu platform online shopping untuk memahami kesempatan dalam meningkatkan pengalaman berbelanja online bagi para pelanggan.